Between vanguard and exclusion - young people of the twenty-first century - Gil, Agnieszka (Journal of Education Culture and Society, 2020)
This study has been narrowed down to reveal aparadox. here the vanguard of cul-ture and civilization - which is regarded as young people of the twenty-first century – is embroiled in adiscourse of exclusion: economic, political and cultural life. in secondary school programs and high schools we do not find specific references and studies, pri-marily based on the needs of students, about the theory of popular culture and cultural education in the area of pop culture. The paradox of exclusion of mainstream culture from educational discourse is schizophrenic. The political exclusion of young people of the xxicentury i consider all the disparaging scientific discourse, which skips the actual media and communication competence of young people. Prosumers, cognitar-chy, digital natives, C-generation – they are for the modern economy “Silicon Valley” - their market power to exclude is already unstoppable. in other areas it remains to be considered whether excluding young people from the cultural discourse will not deprive our future teachers and translators of the next civilization revolution of social reality...